The Influence of Wordpress-Based Interactive Learning Media on Student Learning Outcomes in Sound Wave Material - Saenab T Lasari; Supartin; I Made Hermanto (Universitas Muhammadiyah Palu, 2025)
This study aims to determine the influence of Wordpress-based interactive learning media on student learning outcomes in sound wave material. The population in this study was all students of class XI/4 in the 2024/2025 academic year at SMA Negeri 1 Gorontalo. The data collection techniques was using an instrument in the form of a student learning outcome test sheet, in the form of a multiple-choice test of 30 questions given to students, namely the initial test (pretest) and the final test (posttest).Based on the results of research on the effect of interactive learning media based on wordpress on student learning outcomes on sound wave material, researcher can draw the conclusion that there is an effect of interactive learning media based on wordpress on student learning outcomes on sound wave material. This is shown by the calculation of the paired sample test with a t-count value less than the t-table value or -15.86 < 1.67. Thus, based on the decision-making criteria, H0 is rejected and H1 is accepted, meaning that there is a significant difference in the average learning outcomes between the pretest and posttest data of the experimental class.